The Application of Akad Wakalah Bil Ujrah and Hawalah to Shariah Banking With a Focus on Ijarah Muntahiya Bitamlik and Mudharabah Products in the Perspective of Sharia Economic Law - Rahmat Mulyadin, Hari; Herdiana, Nana; Prasetyo, Yoyok (Zona Law And Public Administration Indonesia, 2024)
The application of sharia principles in banking is very important in the Islamic finance industry. One of the principles used is the wakalah bil ujrah and hawalah contracts, which are used in products such as ijarah muntahiya bitamlik and mudharabah. This article discusses the application of wakalah bil ujrah and hawalah contracts in Islamic banking with a focus on these products from the perspective of Islamic economic law. It will discuss the basic concepts of these contracts, their implementation in ijarah muntahiya bitamlik and mudharabah products, and analyze their compliance with the principles of Islamic economics.